2016
DOI: 10.1111/all.12905
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunotherapy with low allergenic hydrolysed egg in egg allergic children

Abstract: HydE can be regarded as a safe, low allergenic product to use in children allergic to egg. Although not significant, HydE given for 6 months increased numerically the proportion of patients becoming tolerant to egg. HydE induced a modulation of the immune response towards better tolerance. A longer treatment period and/or a higher dose may improve the clinical outcome and should be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 23 publications
4
50
0
1
Order By: Relevance
“…Egg used for OIT can be given (depending on the aim) as pasteurized raw egg white (many adverse events reported), extensively heated egg (boiled white and yolk and/or well‐cooked omelette), and baked egg products . Dehydrated egg white in powder is another possibility …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Egg used for OIT can be given (depending on the aim) as pasteurized raw egg white (many adverse events reported), extensively heated egg (boiled white and yolk and/or well‐cooked omelette), and baked egg products . Dehydrated egg white in powder is another possibility …”
Section: Methodsmentioning
confidence: 99%
“…Egg used for OIT can be given (depending on the aim) as pasteurized raw egg white (many adverse events reported), 67 extensively heated egg (boiled white and yolk and/or well-cooked omelette), and baked egg products. [74][75][76] Dehydrated egg white in powder is another possibility. 74 OIT with peanut has been performed with defatted peanut flour, 20,21 crushed roasted peanuts, 77 and boiled peanuts.…”
Section: Type Of Food In Oitmentioning
confidence: 99%
“…50 A recent pilot study evaluated oral immunotherapy with hydrolysed egg in children. 51 Although a 6-month treatment course in a small number of patients was not enough to demonstrate a statistically significant difference in the proportion of patients who became tolerant to egg, they found that patients treated with hydrolysed egg demonstrated increased specific IgG4 and decreased basophil activation as compared to patients treated with placebo, suggesting a trend toward tolerance.…”
Section: Peptide Immunotherapymentioning
confidence: 99%
“…HydE induced a modulation of the immune response toward better tolerance. A longer treatment period may improve the clinical outcome and should be evaluated …”
Section: Prevention Treatmentmentioning
confidence: 99%
“…A longer treatment period may improve the clinical outcome and should be evaluated. 43 The prevalence of peanut allergy in younger siblings of children with peanut allergy is around 8%, but the anaphylactic risk at the time of introduction is currently unknown, which limits our ability to best counsel parents on this issue. A prospective, double-blinded assessment of risk, diagnostic tests, and an analysis of patient preferences was carried out in 54 peanut-naive younger siblings of peanut-allergic children.…”
Section: Prevention Treatmentmentioning
confidence: 99%